Rizobactérias promotoras de crescimento e mitigação da restrição hídrica em gergelim - Lima, Giliard Bruno Primo de (2021)
The use of microorganisms to mitigate the negative effects of drought has been investigated in some plant species. For sesame (Sesamum indicum L.), an oleaginous species with good phenotypic plasticity, its cultivation has expanded as an off-season crop in the Cerrado and Semiarid regions of Brazil, it is important that studies be conducted to evaluate its performance under little or irregular rainfall distribution, as water stress is a problem that generates imminent losses for small and medium producers, especially in the Northeast region or even in conditions of second crop cultivation, after soy or cotton cultivation. This work aimed to investigate the interaction of bacilli-based inoculants with sesame genotypes under water deficit. The experiment was conducted in a greenhouse at Embrapa Algodão (Campina Grande, PB) with two sesame genotypes (BRS Seda and BRS Anahi) and four inoculants (Bacillus subtilis pant001, ESA 13, ESA 402, and M143) in pots with capacity for 20 L, filled with free-textured soil, previously analyzed at the Soil Laboratory of Embrapa Algodão. The pH and fertility were adjusted according to soil analysis recommendations. The design was completely randomized with five replications and six treatments: (i) without nitrogen (absolute control); (ii) with nitrogen (ammonium sulfate kg ha-1); (iii) four bacilli-based inoculants; with and without water stress. From the 30th day after emergence, watering was suspended for eight days and the plants were subjected to analysis of physiological parameters: stomatal conductance (gs); photosynthesis (A); transpiration (E) and internal CO2 concentration (Ci), using the infrared gas analyzer (IRGA); From the data obtained, the instantaneous efficiency of carboxylation (EiC) and the efficiency of water use (EWA) were calculated. On the last day of water stress, leaves were collected for biochemical analysis [superoxide dismutase, catalase, ascorbate peroxidase, free proline content, nitrogen content, chlorophyll a, b and total (a+b) and carotenoid content]. At the end of the experiment, the agronomic parameters were analyzed: plant height; stem diameter; number of capsules per plant; shoot and root dry mass; and weight of a thousand seeds. Data were analyzed using the SISVAR version 5.7 statistical program, subjected to analysis of variance and comparison of means by the Tukey test (p≤0.05) and submitted to the Shapiro-Wilk normality test. The results revealed a positive effect of inoculants for all agronomic and physiological variables. Leaf nitrogen analysis showed greater accumulation in the stressed treatments, with a significant difference between treatments with and without inoculation. Biochemical measurement showed a significant effect for proline, superoxide demutase, ascorbate peroxidase, catalase and photosynthetic pigments. Considering the final production, the ESA 13 strain established a better interaction with the BRS Anahi genotype and the ESA 402 strain with the BRS Seda genotype, with an increase of 49% and 34%, respectively, for the weight of a thousand seeds, when compared to nitrogen treatment under water stress conditions. Through these data, a potential synergistic effect of the inoculants to the sesame plants is identified, implying a beneficial and bio-sustainable action from a productive chain with growing potential in the world market due to its nutritional quality.